Features of structure formation in crumb rubber modified bitumen - Obukhova Svetlana; Budkina Angelina (E3S Web of Conferences, 2023)
The research is devoted to developing the science-based technological solution for obtaining crumb rubber modified bitumen (CRMB) with improved stability. The technological solution provides a preliminary process of devulcanization of crumb rubber in hydrocarbon plasticizer in the presence of stabilizing agent and subsequent preparation of CRMB. Using fluorescent microscopy, it was established that the formation of a branched structure of crumb rubber is achieved in the waste industrial oil, indicating devulcanization processes. It was found that the most compatible with crumb rubber is a hydrocarbon plasticizer with a high content of naphthenic oil. Synthetic wax was found to be of greater interest as a stabilizing agent, and its application in an amount of 3% allows the formation of a stable CRMB structure and stabilizes the devulcanization process. The test results of obtained CRMB showed that their viscosity corresponds to the requirements for PG bitumen